Salvage pharyngolaryngectomy with total esophagectomy following definitive chemoradiotherapy. Issue 6 (3rd September 2015) - Niwa, Y.; Koike, M.; Fujimoto, Y.; Oya, H.; Iwata, N.; Nishio, N.; Hiramatsu, M.; Kanda, M.; Kobayashi, D.; Tanaka, C.; Yamada, S.; Fujii, T.; et al.
Summary: Historically, total pharyngolaryngectomy with total esophagectomy has been the standard radical surgical treatment for synchronous cancer of the thoracoabdominal esophagus and pharyngolaryngeal region, and for cancer of the cervical esophagus that has invaded as far as the thoracic esophagus. Although definitive chemoradiotherapy that enables preservation of the larynx has often been the first choice of treatment for cancers involving the cervical esophagus, total pharyngolaryngectomy with total esophagectomy is required as a salvage therapy for cases involving failure of complete remission or locoregional recurrence after chemoradiotherapy. However, salvage esophageal surgery after definitive high‐dose chemoradiotherapy is generally associated with high morbidity and mortality. The aim of this study was to examine the short‐term outcome of salvage total pharyngolaryngectomy with total esophagectomy. From 2001 to 2014, nine patients underwent salvage total pharyngolaryngectomy with total esophagectomy at the Department of Gastroenterological Surgery, Nagoya University. The mortality and morbidity rates were high at 22% and 89%, respectively. Four patients (44%) developed tracheal necrosis, which in two patients eventually led to lethal hemorrhage. Salvage total pharyngolaryngectomy with total esophagectomy is an uncommon and highly demanding surgical procedure that should be carefully planned and conducted in selected centers of excellence. Measures must be taken to preserve the tracheal blood supply, thus avoiding fatal complications.